Modelling and forecasting the UK tourism growth cycle in Algarve - Andraz, Jorge Miguel (2009)
Over the past three decades, Portugal has developed a strong economic dependence on tourism, which has several implications for the country's overall economic development. Tourism is an activity that is interrelated strongly with the economic system since Portugal as a whole and specific regions in particular rely on the performance of tourism for their economic activity. Moreover, because economic cycles affect tourism development, it is highly vulnerable to economic fluctuations. Most tourists who visit Portugal are from the European Union, especially Western Europe. Statistics are based on the number of overnight stays in hotel accommodation and other similar establishments. In 2005, the main source markets were the UK (30.7%), Germany (16.5%), Spain (11.5%), the Netherlands (6.8%), France (4.7%), Ireland (3.6%) and Italy (3.1%). These values show that the UK has the greatest share of visitors to Algarve. The purpose of this paper is to propose a modelling approach that best fits the tourism flow pattern in order to support forecasting. The paper contributes to our understanding of the relationship between economic cycles and tourism flows to Portugal (Algarve) and explores the potential of applying the diffusion index model proposed by Stock and Watson (1999, 2002) for tourism demand forecasting.